2018
DOI: 10.1016/j.actpsy.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of disfiguring facial features on overt and covert attention

Abstract: Observers can form negative impressions about faces that contain disfiguring features (e.g., scars). Previous research suggests that this might be due to the ability of disfiguring features to capture attention - as evidenced by contrasting observers' responses to faces with or without disfiguring features. This, however, confounds the effects of salience and perceptual interpretation, i.e. whether the feature is seen as integral to the face, or separate from it. Furthermore, it remains unclear to what extent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The lack of a consistent impact across saccade types suggests that covert attention to the peripherally presented face was not by default affected by these added facial features nor by their type (i.e., whether disfiguring or occluding). This finding is consistent with evidence from our previous study with the same stimuli, in which both peripheral and central faces failed to differentially influence covert attention ( Boutsen et al, 2018 ; Experiments 2 and 3). However, this finding may still surprise as our observers consistently interpreted the disfiguring faces as disease-signalling and as affecting the appearance of the face, more so than they did towards faces with an occluding feature.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The lack of a consistent impact across saccade types suggests that covert attention to the peripherally presented face was not by default affected by these added facial features nor by their type (i.e., whether disfiguring or occluding). This finding is consistent with evidence from our previous study with the same stimuli, in which both peripheral and central faces failed to differentially influence covert attention ( Boutsen et al, 2018 ; Experiments 2 and 3). However, this finding may still surprise as our observers consistently interpreted the disfiguring faces as disease-signalling and as affecting the appearance of the face, more so than they did towards faces with an occluding feature.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, 10 images were created from each face. Details on the faces and on the construction of the added features can be found in Boutsen et al (2018) . Each image was 600 pixels (10.86°) wide and between 703 and 1,007 pixels (12.53–17.88°) tall; aspect ratio was preserved.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2011 ; Fujiwara, 2018 ). Finally, it has been shown that faces with disfigured features attract more fixation on the eyes and incur a higher number of recurrent fixations compared to faces with salience-matched occluding features ( Boutsen et al. , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, FD diverts attention away from internal facial features like the eyes, which plays an important role in social interactions (Rasset et al, 2022a). Clearly, FD affects the allocation of overt visual attention, and not only because of its saliency (Ackerman et al, 2009;Boutsen et al, 2018Boutsen et al, , 2021. In fact, research has shown that faces with FD are not better memorized; people tend to confuse different faces with FD with each other more than different faces without FD (Ackerman et al, 2009).…”
Section: Cognitive Reactionsmentioning
confidence: 99%